Pengaruh Digitalisasi Perbankan Melalui Self Service Technology Terhadap Kepuasan Nasabah Penggunaan Layanan Digital Bank Syariah Pada Bank Syariah Indonesia KCP Kabanjahe - Sahyu Siregar; Riyan Pradesyah (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study was to determine the effect of banking digitization through self-service technology in the form of: Automatic teller machines, Internet Banking and Mobile Banking on customer satisfaction using Islamic bank digital services. The type of research in this paper is quantitative research and the data used is in the form of primary data. Data analysis techniques with descriptive tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Processing of data using the SPSS program version 22.0. The results of this study are that the Automatic Teller Machine (X1) variable has an effect on customer satisfaction as seen from tcount > ttable (5.184>1.967) and its significance level is smaller than 0.05 (0.000<0.05). The Internet Banking variable (X2) has an effect on customer satisfaction as can be seen from tcount > ttable (2.251>1.967) and its significance level is less than 0.05 (0.025<0.05). The Mobile Banking variable (X3) has an effect on customer satisfaction as can be seen from t-count > t-table (6.962>1.967) and its significance level is smaller than 0.05 (0.000<0.05). In banking digitalization in the form of automatic teller machines, internet banking, and mobile banking, it affects customer satisfaction in using Islamic bank digital services at BSI Kabanjahe, which is equal to 0.560 or 56.